Subjective Well Being, Character Strength, Activeness in Participating in Mental Coaching for the Wives of Indonesian Army Soldiers at Kodam I/Bukit Barisan Medan - Sari, Dhedek Ramadhani Permata; Darmayanti, Nefi; Lubis, Rahmi (Journal of Social Work and Science Education, 2025)
This study aims to investigate the influence of mental coaching participation on subjective well-being and character strength among the wives of Indonesian Army (TNI-AD) soldiers. Employing a quantitative research design, the study involved a sample of 330 participants selected through purposive sampling. The level of participation in mental coaching was categorized into active and rarely active groups. Data were analyzed using one-way ANOVA to assess differences between these groups. The results revealed no significant difference in subjective well-being (F = 0.287, p = 0.593) or character strength (F = 0.980, p = 0.323) between the two participation levels. The mean subjective well-being scores were 47.55 for the active group and 47.14 for the rarely active group, while character strength scores were 54.31 and 55.06, respectively. These findings suggest that mental coaching, as currently implemented, does not significantly impact either subjective well-being or character strength among the studied population. The novelty of this study lies in its focus on military spouses a group often overlooked in psychological well-being research and in evaluating the effectiveness of structured mental coaching within a non-clinical setting. Practically, the findings indicate a need to re-evaluate the content and delivery of mental coaching programs to enhance their relevance and effectiveness. This study contributes to the literature on psychological interventions by highlighting the limited impact of generalized coaching programs on targeted psychological constructs within specific social groups.